Laboratory bioefficacy of CREEK 1.0G (tentephos) against Aedes (Stegomyia) aegypti (Linnaeus) lairvae - Chen, C.D.; Lee, H.L. (2006)
The bioefficacy of a commercial formulation of temephos, Creek((R)) againstAedes aegypti larvae was studied in the laboratory. Earthen jars were filled with 10 L tap water each. One g of temephos (Creek((R))) sand granule formulation was added into each earthen jar as recommended by the manufacturer. The final test concentration of Creek((R)) was 1 mg ai./L One earthen jar was filled with 10 L tap water and served as a test control (untreated). Thirty late 3(rd) or early 4(th) instar of lab-bred Ae. aegypti larvae were added into each earthen jar. Mortality of the larvae was recorded after 24 hours and percent mortality was calculated. Test was repeated every week. The results showed that complete larval mortality was achieved after 24 hours. The residual effect lasted 15 weeks (105 days), indicating that Creek((R)) is effective at the dosage recommended by the manufacturer which is 1 mg ai./L.